The impact of presidents’ transformational leadership on faculty occupational well-being—parallel mediating roles of teaching efficacy and job crafting - Sun, TingYu; Luo, Yang; Yoon, Mankeun (Frontiers in Psychology, 2025)
IntroductionOccupational well-being (OW) has gained increasing attention in recent years; however, limited research has focused on university and college faculty—despite their high levels of burnout and job dissatisfaction. This study examines the impact of university presidents’ transformational leadership (TL) on faculty OW, and explores the mediating roles of job crafting and teaching efficacy in this relationship.MethodsA total of 555 faculty members from various higher education institutions in Shandong Province, China, voluntarily participated in an online survey. CB-SEM was applied to examine direct and indirect relationships among the variables, with bootstrapping techniques employed to test mediation effects.ResultsThe results revealed that: (1) presidents’ TL significantly and positively predicted faculty OW; (2) job crafting partially mediated the relationship between TL and OW; and (3) teaching efficacy also partially mediated this relationship.DiscussionThese findings suggest that transformational leadership by university presidents not only directly enhances faculty well-being but also exerts indirect effects through job crafting and teaching efficacy. This study provides valuable insights for higher education administrators seeking to promote faculty well-being through effective leadership strategies.